Rational Design and Facile Synthesis of Dual‐State Emission Fluorophores: Expanding Functionality for the Sensitive Detection of Nitroaromatic Compounds. Issue 4 (29th November 2021) - Chen, Si‐Hong; Luo, Shi‐He; Xing, Long‐Jiang; Jiang, Kai; Huo, Yan‐Ping; Chen, Qi; Wang, Zhao‐Yang
Abstract: Six novel benzimidazole‐based D‐π‐A compounds 4 a –4 f were concisely synthesized by attaching different donor/acceptor units to the skeleton of 1, 3‐bis(1H‐benzimidazol‐2‐yl)benzene on its 5‐position through an ethynyl link. Due to the twisted conformation and effective conjugation structure, these dual‐state emission (DSE) molecules show intense and multifarious photoluminescence, and their fluorescence quantum yields in solution and solid state can be up to 96.16 and 69.82 %, respectively. Especially, for excellent photostability, obvious solvatofluorochromic and extraordinary wide range of solvent compatibility, DSE molecule 4 a is a multifunctional fluorescent probe for the visual detection of nitroaromatic compounds (NACs) with the limit of detection as low as 10 −7 M. The quenching mechanism has been proved as the results of photoinduced electron transfer and fluorescence resonance energy transfer processes. Importantly, probe 4 a can sensitively detect NACs not only in real water samples, but also on 4 a ‐coated strips and 4 a @PBAT thin films. Abstract : Novel benzimidazole‐based D‐π‐A fluorophores are rationally designed and concisely synthesized. Six compounds 4 a –4 f, as dual‐state emission (DSE) materials, exhibit excellent photostability, solvatofluorochromic and extraordinary wide range of solvent compatibility. Among them, the DSE material 4 a is not only reasonably developed as a multifunctional fluorescent probe for sensitive detection of nitroaromatic compounds (NACs) in aqueous system, but also processed into test strips and thin films for visual detection of NACs.